2000
DOI: 10.4049/jimmunol.165.4.2020
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Triggering Selectively Increases TCRBV Gene Transcription

Abstract: When the TCR binds Ag it is phosphorylated, internalized, and degraded. We wished to examine whether this process was accompanied by a specific concomitant increase in TCR mRNA levels. To do this, PBMC and a T cell clone were cultured with a series of superantigens and an alloantigen. Only T cells specifically responding to an antigenic stimulus had increased levels of TCR β-chain variable (TCRBV)-specific mRNA. This response was apparent after 48 h, peaked around 72 h, and was still elevated after 7 days. Inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Immunoscope analysis revealed that most TCRBV found before in vitro restimulation were conserved after in vitro restimulation but also that diversity in terms of TCRBV usage was increased, consistent with the observation that antigen triggering selectively increases TCRBV gene transcription [31]. Besides the number of cells used before and after in vitro restimulation, the difference in RNA extraction yield and in cDNA synthesis could be explained the augmentation of transcripts after in vitro restimulation.…”
Section: Discussionsupporting
confidence: 80%
“…Immunoscope analysis revealed that most TCRBV found before in vitro restimulation were conserved after in vitro restimulation but also that diversity in terms of TCRBV usage was increased, consistent with the observation that antigen triggering selectively increases TCRBV gene transcription [31]. Besides the number of cells used before and after in vitro restimulation, the difference in RNA extraction yield and in cDNA synthesis could be explained the augmentation of transcripts after in vitro restimulation.…”
Section: Discussionsupporting
confidence: 80%
“…These different patterns could have been shaped by thymus selection processes as well as by subtle preimmune constraints in the TCR repertoire (24). Interestingly, whereas T cell activation is characterized by a down-regulation of membranous TCR (25), TCR chain mRNA accumulation is observed (9,26,27). However, V␤ transcript accumulation is the result of a composite regulation depending on both activation (26) and kinetics of T cells infiltrating the graft.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, whereas T cell activation is characterized by a down-regulation of membranous TCR (25), TCR chain mRNA accumulation is observed (9,26,27). However, V␤ transcript accumulation is the result of a composite regulation depending on both activation (26) and kinetics of T cells infiltrating the graft. In the model used in this paper, the infiltrate is maximum on day 5 during rejection and tolerance induction following DST priming (22,28), and T cells are found at similar levels in rejected and tolerated grafts (22, 28, FIGURE 3.…”
Section: Discussionmentioning
confidence: 99%
“…For example, polyclonal expansions of specific V␤ families would not be detected by these methods. To overcome this limitation, we took advantage of the transcriptional activation of the TCR ␤-chain in activated T cells (34,35). For each V␤ family, mRNA accumulation was quantified by real-time RT-PCR, and these values were displayed according to the distribution of CDR3 lengths, as determined by the Immunoscope method (31).…”
Section: Integrated Depiction Of Qualitative and Quantitative Alteratmentioning
confidence: 99%